Isolation and quantification of flavonoids from leaves of moringa oleifera lam and its antioxidant activity - Mohd. Rozi, Nurshahira (2017)
Moringa oleifera Lam. (M. oleifera) which is also called “pokok kelor” is known to be a rich source of flavonoids. Three flavonoids known as isoquercetin, quercetin and kaempferol were isolated from the ethanolic extract of M. oleifera leaves. The compounds were elucidated using spectroscopic methods such as 1H NMR, 13C NMR and FTIR. In a separate study, the different extraction methods of ethanolic extract including cold maceration, soxhlet, ultrasound-assisted by water bath and ultrasound-assisted by probe and solid phase extraction were done. The extracts were subjected to qualitative and quantitative analysis to determine the phytochemicals present in M. oleifera leaf. Qualitative analysis on the extracts showed that M. oleifera contains flavonoid, tannin, alkaloid, phenol, steroid, quinone and coumarin. The result of quantitative analysis was obtained by screening the ethanolic extract for antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl assay, 2,2'azino bis(3-ethylbenzothiozoline-6-sulfonic acid) and ferric reducing antioxidant power assay. Extract from Fraction 2 of solid phase exhibited highest antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl, 2,2'-azinobis(3-ethylbenzothiozoline-6-sulfonic acid) and ferric reducing antioxidant power assay with IC50 of 35.81 µg/mL, IC50 of 41.58 µg/mL and FRAP equivalent of 91.36 mM, respectively. Moreover, the extracts were further analysed using a reversed phase high performance liquid chromatography to quantify the contents of isoquercetin, quercetin and kaempferol. Quantification of isoquercetin, quercetin and kaempferol were found higher using solid phase extraction with 7.98%, 0.86% and 1.11% in w/w%, respectively. The validated HPLC method was effective and practical for quantification of isoquercetin, quercetin and kaempferol in M. oleifera leaf extracts.